Scale-up of biomass production by Methanococcus maripaludis - Palabikyan, Hayk; Ruddyard, Aquilla; Pomper, Lara; Novak, David; Reischl, Barbara; Rittmann, Simon K.-M. R. (Frontiers in Microbiology, 2022)
The development of a sustainable energy economy is one of the great challenges in the current times of climate crisis and growing energy demands. Industrial production of the fifth-generation biofuel methane by microorganisms has the potential to become a crucial biotechnological milestone of the post fossil fuel era. Therefore, reproducible cultivation and scale-up of methanogenic archaea (methanogens) is essential for enabling biomass generation for fundamental studies and for defining peak performance conditions for bioprocess development. This study provides a comprehensive revision of established and optimization of novel methods for the cultivation of the model organism Methanococcus maripaludis S0001. In closed batch mode, 0.05 L serum bottles cultures were gradually replaced by 0.4 L Schott bottle cultures for regular biomass generation, and the time for reaching peak optical density (OD578) values was reduced in half. In 1.5 L reactor cultures, various agitation, harvesting and transfer methods were compared resulting in a specific growth rate of 0.16 h−1 and the highest recorded OD578 of 3.4. Finally, a 300-fold scale-up from serum bottles was achieved by growing M. maripaludis for the first time in a 22 L stainless steel bioreactor with 15 L working volume. Altogether, the experimental approaches described in this study contribute to establishing methanogens as essential organisms in large-scale biotechnology applications, a crucial stage of an urgently needed industrial evolution toward sustainable biosynthesis of energy and high value products.